A comprehensive review on biocompatible thin films for biomedical application. Issue 4 (15th February 2022) - Thanka Rajan, S.; Subramanian, B.; Arockiarajan, A.
Abstract: Thin films have emerged as an ideal surface treatment to the permanent implant materials to enhance properties such as biodegradation resistance, better mechanical strengths and biocompatibility. A perfect implant ought to have the ability of resistance to degradation, stimulate osseointegration, prevent bacterial adhesion, and decrease prosthetic infection. The clinical success of implants depends on the interaction of cells with material surfaces, which is an essential factor. Recent development in biomaterials has brought a variety of coatings on biomaterial to overcome these issues. The coatings impart biocompatibility, better mechanical property, and bioactivity to the biomaterial. In this review, the recent trends in surface modification by thin films of implants have been discussed in detail.